THE FUNCTIONS OF IMPOLITENESS ON ASIA’S LEADING AIRLINE INSTAGRAM - Rudi Anshari .; Rahmad Husein .; Meisuri . . (LINGUISTIK TERAPAN, 2023)
The research aims to investigate the Impoliteness Strategies used in customers complaint on Asia’s leading airline official Instagram account. The objective of this research is to elucidate the functions of Impoliteness Strategies used by customers of Asia’s leading airline in giving online complaints on Instagram. This research employed descriptive qualitative research. The sources of data were taken from 52 customers impolite utterances posted on Asia’s leading airline official Instagram account. The result of this research shows three functions of impoliteness strategies found, Affective Impoliteness (62%), Entertaining Impoliteness (21%), Coercive Impoliteness (17%). The most dominant function used by the customers is Affective Impoliteness which earns 62%. Affective impoliteness is the targeted exhibition of strongly elevated emotion, such as rage or anger, implying that the target is responsible for the bad emotional state. Thirty-three affective impoliteness functions were identified on this airline’s official Instagram comments performed in increased emotion, such as anger, which implicates the production of negative emotions.